PELAKSANAAN PERLINDUNGAN HAK-HAK KOBAN KEKERASAN DALAM RUMAH TANGGA DI KEPOLISIAN RESOR KOTA SIBOLGA - Jusuf Tinambunan; Erdianto Erdianto; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Domestic violence is any act against someone, especially women, which results in suffering or suffering physically, sexually, psychologically, and or neglecting the household, including threats to commit acts, coercion, or deprivation of liberty in the city of Sibolga. not fulfilled.This research is classified into observational research by means of a survey, namely research conducted directly in the research location, namely at the Sibolga Police. Meanwhile, if viewed from its nature, this research is descriptive, namely this research is intended solely to find out a complete, detailed, and clear picture of a reality.The result of this research is that the researcher finds that the Sibolga City Police as the object of the researcher's research still finds an increase in domestic violence from year to year. As for the obstacle to not fulfilling the rights of victims of domestic violence are the factors from the police and the victims themselves, where the police do not socialize the rights of the victims, and the factor of the victims is that the victim does not want to because it is a family disgrace, so efforts are needed to fulfill it. The rights of victims can be provided by a Vocational Training Center (BLK) which is supervised by the Manpower Office, provides a safe house in the police, provided a Crisis Center which is managed by a non-governmental organization (NGO) itself. Keywords: Domestic violence, Protection, Rights of victims